Strategic Decision of Sudimampir Market Traders Banjarmasin in Dealing with Changes in the Business Environment. - Nailiya Nikmah; Julkawait; Nurul Qalbiah; Hikmahwati (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
The business environment is always changing rapidly and continuously because the world has entered the era of economic globalization, politics, the era of information technology, and the era of a management revolution. Changes in the environment cause business units to have to make adjustments to these changes and the competition to use their capabilities to the maximum extent possible, to excel in the competition. Business units make the right decisions in determining strategies that can be used to face competition. This study aims to explain strategic decision-making in dealing with changes in the business environment carried out by traders at Sudimampir Banjarmasin Market. The type of research conducted is descriptive qualitative research. The research was conducted at the Sudimampir Market, conducted from June to November 2022. Based on the results of the study, it can be concluded that the strategic decisions used by the traders of Pasar Sudimampir Banjarmasin in the internal business environment are selling goods not depending on certain brands, maintaining the availability of merchandise, selling goods that are easy to obtain, setting selling prices cheaper than competitors, looking for places strategic business, maintain customer satisfaction with the goods sold, pay attention to the number of employees sufficient to serve buyers and provide good service to attract consumers' interest, maintain the quality of products sold to gain consumer confidence, the availability of sufficient capital to manage the business, and not make loans to increase capital. The strategic decisions used in the external business environment are to pay attention to the ability of consumers to buy and this affects the selling price and quality of the products offered; have a permanent supplier to maintain the quality of the products offered; keep selling offline during the covid-19 pandemic; and offline sales are the main focus of sales and the use of digital technology in sales and promotions carried out by some traders in the Sudimampir Market, Banjarmasin.